THE IMPACT OF IFRS ADOPTION ON DEVELOPING COUNTRIES-A CASE STUDY OF INDIA. - C.Latha; Dr. P. Sridhar (The journal of contemporary issues in business and government, 2022)
The globalization of capital markets has increased the demand for globally unified accounting standards. Regulators think that the International Accounting Standards Board's (IASB) International Financial Reporting Standards (IFRS) provide standardized financial statements. Although a great number of empirical researches looked into the effects of IFRS adoption, the breadth of these studies was limited. This article discusses the harmonization of accounting standards and the overall effects of the implementation of the International Financial Reporting Standards (IFRS) on developing countries.